Probability of a timely vocal response in mother-infant interaction and later psychiatric diagnosis: A case-control study - Bethany Stanley; Clare S. Allely; Jenna Charlton; Christopher Gillberg; James Law; Penny Levickis; Alex McConnachie; Christine Puckering; Lucy Thompson; Philip Wilson (PLoS ONE, 2026)
Patterns of parent-child interactions are commonly cited as being predictive of later psychiatric disorders but precisely which elements of these interactions are important is rarely clear, potentially affecting the effective targeting of interventions in young children. The current study aimed to examine the relationship between timely vocal response during parent-child interactions (i.e., the probability of mothers responding to their child within a specified time period and vice versa), and later psychiatric diagnosis. Drawing on data from the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort, a case control study was conducted based on infant-mother video observations of children assessed for neuropsychiatric disorders using the parent-reported Development and Wellbeing Assessment (DAWBA) at seven years of age (103 controls and 55 cases). Empirical examination suggested that 1 second represented the optimal threshold for maternal responses and 8 seconds for child responses. Only the maternal measure was found to predict later psychiatric disorders, with evidence of associations limited to hyperactivity and conduct disorders. These associations were not sensitive to either maternal education or child sex. The results are discussed in terms of the value of precise interpretation of early mother/child interaction and for the potential for providing targeted intervention to the population concerned.